2020
DOI: 10.21203/rs.3.rs-40074/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of ultrasound artificial intelligence in the differential diagnosis between benign and malignant breast lesions of BI-RADS 4A

Abstract: Background: The classification of Breast Imaging Reporting and Data System 4A (BI-RADS 4A) lesions is mostly based on the personal experience of doctors and lacks specific and clear classification standards. The development of artificial intelligence (AI) provides a new method for BI-RADS categorisation. We analysed the ultrasonic morphological and texture characteristics of BI-RADS 4A benign and malignant lesions using AI, and these ultrasonic characteristics of BI-RADS 4A benign and malignant lesions were co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…BI‐RADS 4a lesions mainly include some atypical benign and malignant lesions, with a malignant rate of 2–10% 8 . Niu et al used artificial intelligence technology to analyze the US morphology and texture characteristics of category 4a breast lesions and concluded that more calcifications would be found in benign breast lesions 32 . This characteristic increases uncertainty to the assessment of benign breast lesions and makes these lesions less typical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BI‐RADS 4a lesions mainly include some atypical benign and malignant lesions, with a malignant rate of 2–10% 8 . Niu et al used artificial intelligence technology to analyze the US morphology and texture characteristics of category 4a breast lesions and concluded that more calcifications would be found in benign breast lesions 32 . This characteristic increases uncertainty to the assessment of benign breast lesions and makes these lesions less typical.…”
Section: Discussionmentioning
confidence: 99%
“…8 Niu et al used artificial intelligence technology to analyze the US morphology and texture characteristics of category 4a breast lesions and concluded that more calcifications would be found in benign breast lesions. 32 This characteristic increases uncertainty to the assessment of benign breast lesions and makes these lesions less typical. Therefore, it may affect the final result to consider the category 4a breast lesions as malignant or benign.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) demonstrated, using nearly 130,000 clinical images, that CNNs are capable of classifying skin cancers with a level of competence comparable to expert dermatologists (Esteva et al., 2017). Promising results regarding cancer diagnosis were also reported in other types of cancer including lung, breast, brain and colon (Attardo et al., 2020; Cho et al., 2020; Niu et al., 2020; Sathyakumar et al., 2020).…”
Section: Introductionmentioning
confidence: 91%
“…33 This is probably related to the biological behavior of the tumor. 34 As high-grade tumors grow rapidly and nonuniformly, their shapes appear to be irregular or lobulated, whereas low-grade tumors tend to grow slowly and parallelly, resulting in smooth margins.…”
Section: Discussionmentioning
confidence: 99%